2009
DOI: 10.1073/pnas.0900965106
|View full text |Cite
|
Sign up to set email alerts
|

Craniosynostosis in the Middle Pleistocene human Cranium 14 from the Sima de los Huesos, Atapuerca, Spain

Abstract: We report here a previously undescribed human Middle Pleistocene immature specimen, Cranium 14, recovered at the Sima de los Huesos (SH) site (Atapuerca, Spain), that constitutes the oldest evidence in human evolution of a very rare pathology in our own species, lambdoid single suture craniosynostosis (SSC). Both the ecto-and endo-cranial deformities observed in this specimen are severe. All of the evidence points out that this severity implies that the SSC occurred before birth, and that facial asymmetries, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 50 publications
1
55
0
5
Order By: Relevance
“…The study of the spheno-occipital and jugular synchondroses showed that the cranium had not reached adulthood, and that the death of the hominid happened around 10-12 years of age. CT reconstruction also ascertained that the intracranial volume of Cranium 14 was approximately 1,200 cm 3 [23]. In addition, the internal surface of the specimen showed marked endocranial convolutions and signs of enlarged subarachnoid spaces, which have been also documented in cases of positional plagiocephaly and of true craniosynostosis [15,30,38].…”
Section: "Benjamina": the Middle Pleistocene Child With True Lambdoidmentioning
confidence: 76%
See 4 more Smart Citations
“…The study of the spheno-occipital and jugular synchondroses showed that the cranium had not reached adulthood, and that the death of the hominid happened around 10-12 years of age. CT reconstruction also ascertained that the intracranial volume of Cranium 14 was approximately 1,200 cm 3 [23]. In addition, the internal surface of the specimen showed marked endocranial convolutions and signs of enlarged subarachnoid spaces, which have been also documented in cases of positional plagiocephaly and of true craniosynostosis [15,30,38].…”
Section: "Benjamina": the Middle Pleistocene Child With True Lambdoidmentioning
confidence: 76%
“…Deformational posterior plagiocephaly was discovered in 93 instances (12.48%) and true lambdoid synostosis in 13 (1.74%) cases [33]. There is also a mention to the high frequency of craniosynostosis in skulls recovered from the cemetery of St. James and St. Mary Magdalene Medieval Hospital in Chichester, England, that functioned as an almshouse since 1450 AD, where children with congenital defects were abandoned [23].…”
Section: Craniosynostosis Throughout the Historymentioning
confidence: 99%
See 3 more Smart Citations